A REVIEW OF RABIES IN LIVESTOCK AND HUMANS IN ETHIOPIA - Oyda, Semayat; Megersa, Bekele (International Journal of Research -GRANTHAALAYAH, 2017)
Rabies, a viral disease caused by lyssa virus of family Rhabdoviridae, is a fatal zoonotic disease with worldwide occurrence and endemic in developing countries of Africa and Asia. Rabies generally affects all warm-blooded animals, but it is primarily a disease of dogs in Ethiopia because access to suspected domestic canids and pets are not controlled indoor or by immunization. The major means of transmission of the disease is through any types of bite, scratch, or other situation in which saliva, cerebral, spinal fluid, tear, or nervous tissues from suspected or known rabid animal or person enters an open wound, is transplanted into, or comes in contact with mucus membrane of another animals or person. One of retrospective study of rabies in Addis Ababa from 1990 – 2000 indicated that an average of 2,200 people per year received post – exposure antirabies treatment while 95% of the reported fatal human rabies case was due to dog bites. The widespread use of traditional medicine among urban and rural population of Ethiopia could be attributed to cultural acceptability, physical accessibility and economic affordability. Individuals who are exposed to the rabies virus often see traditional healers for the diagnosis and treatments of the disease. Once the virus entered into body of exposed individuals through wound (abrasion) or direct contact with mucosal surface, then there, it replicates in the site of deposit (bitten site), where local viral proliferation occurs, and get access (viral attachment) to motor endplates. The clinical sign of the disease is nonspecific and difficult to differentiate without laboratory test, but some of signs such as pupil dilation in some case, paralysis (last stage) and hydrophobia are some characteristic signs. The control of access to domestic canid to other suspected animals is not only prevention method but also is treatment measures. Mass vaccination of dogs and removal of stray canids are the best measure of control. In general, this study provides an overview of the current status of Rabies in livestock and human in Ethiopia.